Concomitant Use of Carbamazepine and Rifampin in a Patient With Mycobacterium avium Complex and Seizure Disorder. (June 2014) - Egelund, Eric F.; Mohamed, MohamedEslam F.; Fennelly, Kevin P.; Peloquin, Charles A.
Objectives . To report a probable interaction between rifampin and carbamazepine, likely leading to a seizure, and to review conflicting reports regarding this interaction.Case Summary . A 55-year-old female was treated with carbamazepine 200 mg 3 times daily for grand mal seizures, with excellent control. A 6-hour postdose carbamazepine concentration was 10.7 µg/mL (therapeutic range = 4-10 µg/mL). After she was diagnosed with pulmonary Mycobacterium avium complex, she received rifampin 300 mg twice daily, ethambutol 800 mg daily, and clarithromycin 500 mg twice daily. At first clinic visit, rifampin was changed to 600 mg daily, and clarithromycin was replaced with azithromycin 250 mg daily. A 4-hour postdose carbamazepine concentration was 7.1 µg/mL. Two weeks later, the patient experienced a seizure (no carbamazepine concentration reported at that time), but admitted to missing doses of carbamazepine. After experiencing 2 more seizures, the patient stopped taking rifampin. Subsequently, the carbamazepine dose was increased to 400 mg twice daily and rifampin was restarted at 600 mg daily. Two follow-up peak carbamazepine concentrations were 4.7 µg/mL and 4.4 µg/mL, with no reported seizures. No additional factors were identified as potential causes of the seizures or the lower carbamazepine concentrations. A Drug Interaction Probability Scale score of 6 indicates a probable interaction.Discussion . Conflicting reports exist regarding the effect of rifampin on carbamazepine concentrations, likely reflecting rifampin's ability to display time-dependent, mixed effects on transporters and cytochrome P450 enzymes.Conclusions . Our case report describes a patient who experienced seizures after the addition of rifampin to her regimen, followed by lower peak concentrations of carbamazepine. Therapeutic drug monitoring in patients receiving both rifampin and carbamazepine is recommended to help clinicians optimize drug therapy.